Penggunaan Aplikasi Tiktok bagi Remaja Karang Taruna dalam Membentuk Perilaku Sosial di Desa Tanjung Tambak Baru Kabupaten Ogan Ilir Provinsi Sumatera Selatan - Dewanti Putri, Meytari; Isnawijayani, Isnawijayani; Santhi Zinaida, Rahma; Hafizni, Moh. (EduInovasi: Journal of Basic Educational Studies, 2025)
This study aims to describe the use of the TikTok application by youth in shaping social behavior in Tanjung Tambak Baru Village, Ogan Ilir Regency, South Sumatra Province. This study was conducted using a descriptive qualitative method. The research subjects were a group of youth aged 21-23 years who actively use social media, namely the TikTok application. The primary data in this study is a collection of information obtained through interviews, observations, and documentation, while secondary data includes various literature that has relevance to the research object. Furthermore, the collected data was analyzed carefully and continuously using interactive analysis techniques. Based on the results of the study, it can be concluded that the use of the TikTok application by youth in Karang Taruna in Tanjung Tambak Baru Village plays an important role in shaping their social behavior, especially in terms of communication style, level of creativity, and involvement in social activities. Social media, especially TikTok, has been shown to have a significant influence on these aspects